Educative software using by Rehabilitation teachers, Holguín. September 2019- January 2020: Empleo de software educativo por los profesores de Rehabilitación, Holguín. Septiembre 2019 - enero 2020 - Gutiérrez-Segura, Mildred (2020)
Objective: Describe software educative using by Rehabilitation I and II professors in dentistry major. Materials and methods: An observational, cross, descriptive research was carried out at medical university in Holguin, from September 2019 to January 2020, with no probabilistic intentional sample that included eight professors of Rehabilitation I and II  signatures. Dialectic was used as a theoretical method, besides logic and historic, analysis and synthesis and induction and deduction. Observation, documental analysis and a questionnaire were the empiric methods.  Statistical analysis permit processing the information and showing the results in percent and complete values. Results:  50% of the professors used educative software in someone classes, six ot them in the development. 62,5% of the professors using them in the independent work, 50% in workshop classes, 87,5% direct  independent study,  75% discuss contents,  62,5% motivate and 50% promote team work, making exercises and viewing pictures.  Conclusions: Educative software using should increase to approach whole possibilities of these resources, this is a way to contribute for knowledge independency in the students. Keywords: educative software, rehabilitation, informatics programs, teaching, learning, dentistry.